Investigating the Effectiveness of Choice Theory Training on Time Perspective and Psychological Capital (Resilience, Self-Efficacy, Hope, and Optimism) in Male High School Students in South Khorasan Province - Hamidi, Hadi; Kamyabi, Mitra; Manzari Tavakkoli, Alireza; Zeinaddini Meymand, Zahra (International Journal of Education and Cognitive Sciences, 2025)
Purpose: The present study aimed to analyze the effectiveness of choice theory training on time perspective and psychological capital in male high school students in South Khorasan Province. Methods and Materials: This study was conducted using a quasi-experimental design with a pre-test, post-test, and follow-up phase across three groups (for each dependent variable). The statistical population consisted of all male high school students in South Khorasan Province. A purposive and convenient sampling method was used to select participants. The statistical population was divided into three groups of 15 participants, and choice theory training was conducted with them. The Zimbardo Time Perspective Inventory (ZTPI) by Zimbardo and Boyd (1999) and the Psychological Capital Questionnaire (PCQ) by Luthans (2007) were used to evaluate the outcomes. The research hypotheses were analyzed using repeated-measures ANCOVA. Findings: The results indicate that choice theory training impacts the components of negative past, positive past, hedonistic present, and fatalistic present. Furthermore, effect size values show that choice theory training created the necessary effectiveness within the groups. The training also influenced the components of self-efficacy, hope, resilience, and optimism. Similarly, effect size values demonstrate that the training established the required effectiveness among the groups. Conclusion: The results of this study revealed that choice theory training can significantly assist students in acquiring essential characteristics. Time perspective and psychological capital are critical attributes of a successful and mentally healthy student, which can be fostered through choice theory training.